Impact of the Polymorphism rs9264942 near the HLA-C Gene on HIV-1 DNA Reservoirs in Asymptomatic Chronically Infected Patients Initiating Antiviral Therapy - Laura Herráiz-Nicuesa; Diana Carolina Hernández-Flórez; Lara Valor; Sonia García-Consuegra; Juan Paulo Navarro-Valdivieso; Eduardo Fernández-Cruz; Carmen Rodríguez-Sainz (Journal of Immunology Research)
Several genome-wide association studies have identified a polymorphism located 35 kb upstream of the coding region of HLA-C gene (rs9264942; termed −35 C/T) as a host factor significantly associated with the control of HIV-1 viremia in untreated patients. The potential association of this host genetic polymorphism with the viral reservoirs has never been investigated, nor the association with the viral control in response to the treatment. In this study, we assess the influence of the polymorphism −35 C/T on the outcome of virus burden in 183 antiretroviral-naïve HIV-1-infected individuals who initiated antiviral treatment (study STIR-2102), analyzing HIV-1 RNA viremia and HIV-1 DNA reservoirs. The rs9264942 genotyping was investigated retrospectively, and plasma levels of HIV-1 RNA and peripheral blood mononuclear cell- (PBMC-) associated HIV-1 DNA were compared between carriers and noncarriers of the protective allele −35 C before antiretroviral therapy (ART), one month after ART and at the end of the study (36 months). HIV-1 RNA and HIV-1 DNA levels were both variables significantly different between carriers and noncarriers of the allele −35 C before ART. HIV-1 DNA levels remained also significantly different one month posttherapy. However, this protective effect of the −35 C allele was not maintained after long-term ART.